उच्चतर लेखांकन - Jain, P.K.; Soni, M.L. (Madhya Pradesh Hindi Granth Academy, 2015)
The book is based on various concepts and practices in Advanced Accounting.
Advanced Accounting
Keywords: Accounting; Hindi; Hindi